2005
DOI: 10.1111/j.1365-2958.2005.04914.x
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of penicillin resistance in Streptococcus pneumoniae reveals a novel role for PstS, a subunit of the phosphate ABC transporter

Abstract: SummaryResistance to penicillin is widespread in the Grampositive bacterium Streptococcus pneumoniae , and while several mutations are known to be implicated in resistance other mechanisms are likely to occur. We used a proteomic screen of two independent mutants in which resistance was selected in vitro . We found a number of differentially expressed proteins including PstS, a subunit of the phosphate ABC transporter of S. pneumoniae . This protein was increased in both mutants, a phenotype correlated to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
(60 reference statements)
0
42
1
2
Order By: Relevance
“…Cultures were incubated for 16-24 h in a 5% CO 2 atmosphere at 37°C. In order to select resistant cells, we subcultured R6 or CCRI 1974 in medium containing increasing concentration gradients of linezolid as described previously for other antibiotics (Martineau et al 2000;Soualhine et al 2005). Mutants were selected in a stepwise fashion by picking colonies growing at the highest antibiotic concentration at each stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were incubated for 16-24 h in a 5% CO 2 atmosphere at 37°C. In order to select resistant cells, we subcultured R6 or CCRI 1974 in medium containing increasing concentration gradients of linezolid as described previously for other antibiotics (Martineau et al 2000;Soualhine et al 2005). Mutants were selected in a stepwise fashion by picking colonies growing at the highest antibiotic concentration at each stage.…”
Section: Methodsmentioning
confidence: 99%
“…For episomal expression, the entire coding sequences of genes of interest were PCR amplified with primers containing BamHI and XbaI and cloned into the S. pneumoniae-E. coli shuttle vector pDL289 (Buckley et al 1995), a kind gift of D. Cvitkovitch (University of Toronto). The plasmid DNAs (2 mg) were introduced in S. pneumoniae in which competence was induced using a competence peptide as described (Soualhine et al 2005). Transformants were selected in media containing 500 mg/ mL kanamycin.…”
Section: Dna Constructsmentioning
confidence: 99%
“…P. mirabilis HI4320 possesses a pst operon identical in gene organization to that observed in Escherichia coli. Previous studies have suggested that the roles of the Pst transport system in pathogenesis include regulation of invasion (Lucas et al, 2000;Mathew et al, 2001;Sinai & Bavoil, 1993), antibiotic resistance (Soualhine et al, 2005), colonization (Buckles et al, 2006;Daigle et al, 1995;Lamarche et al, 2005;Orihuela et al, 2001;Peirs et al, 2005;Runyen-Janecky et al, 2005), and biofilm formation (Monds et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…P. mirabilis HI4320 possesses a pst operon identical in gene organization to that observed in Escherichia coli. Previous studies have suggested that the roles of the Pst transport system in pathogenesis include regulation of invasion (Lucas et al, 2000;Mathew et al, 2001;Sinai & Bavoil, 1993), antibiotic resistance (Soualhine et al, 2005), colonization (Buckles et al, 2006;Daigle et al, 1995;Lamarche et al, 2005;Orihuela et al, 2001;Peirs et al, 2005;Runyen-Janecky et al, 2005), and biofilm formation (Monds et al, 2001).Since (i) earlier work has alluded to the importance of this system during biofilm formation (Monds et al, 2001(Monds et al, , 2007 and (ii) the formation of crystalline biofilms is a characteristic of UTIs associated with P. mirabilis, we hypothesized that the Pst system of P. mirabilis HI4320 is involved in biofilm formation during establishment of a UTI. To assess the role of the Pst system, this study focused upon determining previously undetected in vitro phenotypes of the Dpst mutants by comparing biofilm formation between the wild-type HI4320 and DpstA and DpstS mutants via confocal laser scanning microscopy (CLSM) and quantitative analysis of surface coverage, and by comparing in vitro protein expression of these strains grown planktonically and as a biofilm.…”
mentioning
confidence: 99%
“…Moreover, ABC transporters together with neighboring two-component systems, which regulate their expression, could coevolve to form self-sufficient detoxification modules against antimicrobial peptides in Firmicutes bacteria (44). A significant correlation between penicillin resistance and upregulation of ABC transporters was also reported (45). These studies indicate that the overexpression of ABC transporters might also be involved in CRO resistance by enhancing the activity of drug transport.…”
Section: Discussionmentioning
confidence: 70%